ERAS® protocol improves survival after radical cystectomy: A single-center cohort study. Issue 35 (2nd September 2022) - Crettenand, François; M'Baya, Olivier; Grilo, Nuno; Valerio, Massimo; Dartiguenave, Florence; Cerantola, Yannick; Roth, Beat; Rouvé, Jean-Daniel; Blanc, Catherine; Lucca, Ilaria
Abstract : Introduction: To evaluate Enhanced recovery after surgery (ERAS®) protocol on oncological outcomes for patients treated with radical cystectomy (RC) for urothelial carcinoma of the bladder (UCB). Methods: A prospectively maintained single-institutional database comprising 160 consecutive UCB patients who underwent open RC from 2012 to 2020 was analyzed. Patients receiving chemotherapy and those with a urinary diversion other than ileal conduit were excluded. Patients were divided into two groups according to the perioperative management (ERAS® and pre-ERAS®). The study aimed to evaluate the impact of the ERAS® protocol on survival at five years after surgery using a Kaplan–Meier log-rank test. A multivariable Cox proportional hazards model was used to identify prognostic factors for cancer-specific (CSS) and overall survival (OS). Results: Of the 107 patients considered for the final analysis, 74 (69%) were included in the ERAS® group. Median follow-up for patients alive at last follow-up was 28 months (interquartile range [IQR] 12–48). Five-years CSS rate was 74% for ERAS® patients, compared to 48% for the control population ( P = 0.02), while 5-years OS was 31% higher in the ERAS® (67% vs. 36%, P = .003). In the multivariable analysis, ERAS® protocol and tumor stage were independent factors of CSS, while ERAS®, tumor stage so as total blood loss were independent factors for OS. Discussion: A dedicated ERAS® protocol for UCB patients treated with RC has a significant impact on survival. Reduction of stress after a major surgery and its potential improvement of perioperative patient's immunity may explain these data.